2018
DOI: 10.1111/fare.12345
|View full text |Cite
|
Sign up to set email alerts
|

Social Services Professionals' Views of Barriers to Supporting Homeless Noncustodial Fathers

Abstract: Objective To investigate barriers to service for homeless non-custodial fathers from the perspective of social service professionals who work directly to assist men with securing housing while meeting the demands of fatherhood. Background The population of homeless fathers in the United States is increasing. Longitudinal studies show that although homeless noncustodial fathers and mothers face similar risk factors and barriers to services, research on minimizing risk factors and barriers for noncustodial fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…This young father’s commitment to his daughter’s well-being and willingness to double his efforts so as to somehow financially support yet another child serve as a noteworthy counterexample to the common portrayal of young street-involved men as “deadbeat dads” (Fagan & Lee, 2011; Rogers & Rogers, 2019). At the same time, by stating that he will keep on trying “harder and harder,” this young father exemplifies what young street-involved fathers might be panicking about when they do flee from such scenarios.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This young father’s commitment to his daughter’s well-being and willingness to double his efforts so as to somehow financially support yet another child serve as a noteworthy counterexample to the common portrayal of young street-involved men as “deadbeat dads” (Fagan & Lee, 2011; Rogers & Rogers, 2019). At the same time, by stating that he will keep on trying “harder and harder,” this young father exemplifies what young street-involved fathers might be panicking about when they do flee from such scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…asshole republican shit”), determined to keep on controlling female sexuality and bodies, views street-involved pregnancies as only involving the mother and the fetus, and if born, child. Although society is harshly condemning men for fleeing their responsibilities (Rogers & Rogers, 2019), it is meant as a deterring message for young women about the risks of nonmarital sex, young street-involved men are neither encouraged to stay and father nor supported if they do try to do so.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative data obtained from these interviews will be recorded, transcribed and analysed using Hatch's methods as previously used by our team. [31][32][33] Lastly, Objective 3 (Years 1 and 2) will first focus on intervention development, which will be informed by integrating (1) the findings of Objectives 1 and 2 (quantitative +qualitative), (2) community action board (CAB) input, and (3) the Behaviour Change Wheel (BCW), 34 a step-by-step intervention development approach that uses theory and evidence-based methods to identify and address barriers. We will then pilot the iBeatCRC intervention, which may be based on a multicomponent media campaign, as endorsed by the Community Preventive Services Task Force for promoting CRC screening among individuals aged 50 years and over.…”
Section: Methods and Analysis Study Background And Research Designmentioning
confidence: 99%
“…Consequently, there is a gap in the literature about provision of social and parenting services for this subpopulation. Rogers and Rogers (2019) have begun to address this gap in the literature by examining the perspectives of social service professionals who work with homeless fathers. The providers reported that many fathers had lost trust in the entire social service system after negative experiences with child support officials and child protective services (Rogers & Rogers, 2019).…”
Section: Social Service Needsmentioning
confidence: 99%